(untitled) (Research, Society and Development, 2020)
The accelerated growth of Brazilian cities in the twentieth century did not have the same rhythm of planning and territorial planning, which triggered problems of urban order, such as land irregularity. This informality affects social, urban, social and legal damages, especially when it comes to areas occupied by the population with lower resources, since these usually have more fragile configurations. The objective of this article is to analyze the social and spatial characteristics of the Tôta Barbosa Urban Social Interest Center submitted to land regularization in 2018, in order to discuss the particularities of areas classified in this category. This research is qualitative, is characterized as exploratory descriptive and uses the case study, adopting as methodological procedures the monitoring of activities and access to the database produced by the Program Access to Urbanized Land between 2015 and 2018, the realization interviews with residents of Tôta Barbosa and the execution of on-site visits. It was verified that the urban nucleus Tôta Barbosa presents a linearity in the formation of blocks and the standardization of the dimensions of the streets; has urban public facilities; occupation is predominantly for housing purposes; the basic infrastructure includes fragilities of drainage of rainwater, supply of drinking water, sewage and roads; in the case of income, this area presents greater vulnerability of income than the municipal indexes and the irregular areas at national level. These aspects suggest the adoption of a priority of directing programs of housing improvements and social assistance.